The cost of inaction on preconception health in Nigeria: An economic impact analysis - Sébastien Poix; Khalifa Elmusharaf (Taylor & Francis Group, 2024)
A growing body of evidence has shown the effects of poor preconception health on adverse pregnancy outcomes and, subsequently, maternal and child morbidity and mortality. However, the cost of poor preconception health remains relatively unexplored. Using the case of Nigeria, this study provides the first estimate of the disease and economic burden of poor preconception health at a country level. Using data from international databases and the scientific literature, the study used a cost-of-illness approach to quantify the foregone productivity and direct healthcare costs resulting from six preconception risk factors (adolescent pregnancy, short birth interval, overweight and obesity, intimate partner violence, female genital mutilation, folate deficiency). The results indicate that 6.7% of maternal deaths, 10.9% of perinatal deaths, and 10.5% of late neonatal deaths were attributable to the selected preconception risk factors in 2020. The economic burden of poor preconception health in Nigeria was estimated at US$ 3.3 billion in 2020, of which over 90% was generated by premature mortality. If prevalence rates remain constant, total economic losses could amount to US$ 46.2 billion by 2035. This analysis paves the way for further studies investigating the economic costs and benefits of preconception interventions and policies in low and middle-income countries.